APLIKASI FRONT OFFICE BERBASIS QR CODE DI DINAS KESEHATAN PROVINSI KALIMANTAN TENGAH - Rian, Rian; Ichsan, Moch.; Dhalin, Dhalin; Veronika, Fitri (Jurnal Ilmiah Sistem Informasi, 2023)
The practical field work (PKL) that we have carried out at the Central Kalimantan Provincial Health Service provides students with understanding, skills and creativity in being responsible for the tasks given as well as providing knowledge and new things in knowing the real world of performance that occurs in the field. As with the use of technology, it must be able to continue to be developed to speed up and make it easier to complete a job. As the era of recording guest books progresses, the list of visits and complaints which are still manualized can be transferred using developing technology such as using websites or applications. Likewise, the Central Kalimantan provincial health service still uses manual guest book recording using books. For this reason, we as PKL students created an application, namely Front Office, to make it easier for officers to serve guests visiting the Central Kalimantan Provincial Health Service. Apart from that, the website created is expected to make it easier to record guest books, visits and complaints at the Central Kalimantan Provincial Health Service